Fecal microbiome transplantation and tributyrin improves early cardiac dysfunction and modifies the BCAA metabolic pathway in a diet induced pre-HFpEF mouse model - Hatahet, Jomana; Cook, Tyler M.; Bonomo, Raiza R.; Elshareif, Nadia; Gavini, Chaitanya K.; White, Chelsea R.; Jesse, Jason; Mansuy-Aubert, Virginie; Aubert, Gregory (Frontiers in Cardiovascular Medicine, 2023)
More than 50% of patients with heart failure present with heart failure with preserved ejection fraction (HFpEF), and 80% of them are overweight or obese. In this study, we developed an obesity-associated pre-HFpEF mouse model and showed an improvement in both systolic and diastolic early dysfunction following fecal microbiome transplant (FMT). Our study suggests that the gut microbiome-derived short-chain fatty acid butyrate plays a significant role in this improvement. Cardiac RNAseq analysis showed butyrate to significantly upregulate ppm1k gene that encodes protein phosphatase 2Cm (PP2Cm) which dephosphorylates and activates branched-chain α-keto acid dehydrogenase (BCKDH) enzyme, and in turn, increases the catabolism of branched-chain amino acids (BCAAs). Following both FMT and butyrate treatment, the level of inactive p-BCKDH in the heart was reduced. These findings show that gut microbiome modulation can alleviate early cardiac mechanics dysfunction seen in the development of obesity-associated HFpEF